2020
DOI: 10.1007/s00109-020-01904-z
|View full text |Cite
|
Sign up to set email alerts
|

ER stress activates immunosuppressive network: implications for aging and Alzheimer’s disease

Abstract: The endoplasmic reticulum (ER) contains stress sensors which recognize the accumulation of unfolded proteins within the lumen of ER, and subsequently these transducers stimulate the unfolded protein response (UPR). The ER sensors include the IRE1, PERK, and ATF6 transducers which activate the UPR in an attempt to restore the quality of protein folding and thus maintain cellular homeostasis. If there is excessive stress, UPR signaling generates alarmins, e.g., chemokines and cytokines, which activate not only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 206 publications
(274 reference statements)
3
51
0
Order By: Relevance
“…The situation is reminiscent of the compensatory immunosuppression encountered in inflammatory diseases (see above). It is also known that different cellular stresses, e.g., oxidative stress and ER stress, are potent inducers of inflammation which enhances the differentiation and expansion of immunosuppressive MDSCs [ 60 62 ]. Ruhland et al [ 20 ] demonstrated that the upregulation of senescent stromal cells in mouse skin provoked inflammation which promoted the appearance of an immunosuppressive microenvironment, i.e., senescent cells augmented the levels of MDSCs and Tregs in mouse skin.…”
Section: Cellular Senescence Promotes Inflammaging and Immunosuppressmentioning
confidence: 99%
“…The situation is reminiscent of the compensatory immunosuppression encountered in inflammatory diseases (see above). It is also known that different cellular stresses, e.g., oxidative stress and ER stress, are potent inducers of inflammation which enhances the differentiation and expansion of immunosuppressive MDSCs [ 60 62 ]. Ruhland et al [ 20 ] demonstrated that the upregulation of senescent stromal cells in mouse skin provoked inflammation which promoted the appearance of an immunosuppressive microenvironment, i.e., senescent cells augmented the levels of MDSCs and Tregs in mouse skin.…”
Section: Cellular Senescence Promotes Inflammaging and Immunosuppressmentioning
confidence: 99%
“…Furthermore, it was shown that the MDSCs induce the increase of Tregs [170,183]. In this way, there is an immunosuppressive network which is created as individuals are aging as coined by Salminen et al [184]. It seems that TGF-β, IL-10, and NO, secreted by MDSCs, are the major soluble mediators maintaining the functions of this age-related immunosuppressive network [185].…”
Section: Immunosuppressive Mechanismsmentioning
confidence: 99%
“…Together, the immunosuppressive network increase with aging may have several pathological consequences [184,185], but however, in the spirit of immunobiography, this can also be considered an adaptation to decrease the lifelong activation process of the innate immune system (innate immune memory) but unfortunately in the meantime downregulate adaptive immune activation.…”
Section: Immunosuppressive Mechanismsmentioning
confidence: 99%
“…Like aging processes, cancers environment is characterized by a chronic inflammation (“inflammaging”) and cellular senescence (“immunosenescence”). The role of stromal cells’ immunomodulation in shaping a senescent microenvironment in broad spectrum of human malignancies, especially tumorigenesis, has been documented extensively [for review see Salminen et al (2020) , Thomas et al (2020) ]. For instance, BM stromal cells from patients with myelodysplastic syndrome display a senescence phenotype induced by S100A9-induced Toll-like receptor 4 (TLR4), NLRP3 inflammasome activation and IL-1β secretion ( Shi et al, 2019 ).…”
Section: Msc Pro-tumorigenic Effects: Immunosuppression and Metabolicmentioning
confidence: 99%